Propaganda, Communication and Public Opinion - Smith, Bruce Lannes; Lasswell, Harold D. (Princeton, NJ : Princeton University Press, 2015)
"The most comprehensive bibliography yet published in the public opinion field." -Journalism Quarterly. Besides a selection of the most significant titles from earlier years, this book contains a comprehensive listing of books, pamphlets, and articles which appeared between 1934 and 1943.Originally published in 1946.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Acknowledgments -- Table of Contents -- The Science of Mass Communication: Four Essays -- Introduction -- Communication Channels / Casey, Ralph D. -- The Political Communication Specialist of Our Times / Smith, Bruce Lannes -- Describing the Contents of Communications / Lasswell, Harold D. -- Describing the Effects of Communications / Lasswell, Harold D. -- Bibliography -- One Hundred and Fifty Outstanding Titles on Propaganda, Communication, and Public Opinion -- Outstanding Titles on the Art and Science of Popularization -- Organization of Bibliography -- General Bibliography -- Author and Subject Index to Bibliography
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Propaganda -- Bibliography; Public opinion -- Bibliography; Public relations -- Bibliography; Publicity -- Bibliography; POLITICAL SCIENCE / Propaganda